Towards an Articulation between the Marxist Theory of Value and the Theory of Communicative Action by Jürgen Habermas (2019)
The purpose of this article is to highlight the relevance of the Marxist perspective of value-work in the Theory of Communicative Action by J. Habermas. In this way, it is a question of debunking or relativizing the frequent interpretation that judges Habermas’s approach to be alien and even contrary to Marxism. This does not mean that the two theories simply are coupled in perfect harmony. It is not difficult to find criticism of Marx’s thinking in some Habermasian lines. At the same time, it is recognized that, from a Marxist stance, it is possible to point important limits and problems to the Habermasian proposal. In short, our writing tries to justify the need to deepen an articulation between the two theoretical productions in order to enrich the analysis of the social world from a critical orientation.